EFEK PEREKAT GETAH DAMAR TERHADAP KARAKTERISTIK PERPINDAHAN PANAS DALAM PROSES PEMBAKARAN BRIKET SARANG LEBAH AMPAS SAGU - Haurissa, Jusuf; Foisa, Benhard (DINAMIS, 2023)
This research aims to evaluate the ignition quality of briquettes made from sago waste and coconut shells and determine the heat transfer rate in the combustion process of briquettes using damar resin as a binder through conduction and convection. The research method employed laboratory experiments, utilizing two testing models: honeycomb briquettes with 14 holes made from sago waste, coconut shells with damar resin as a binder, and a similar honeycomb briquette model using tapioca flour as a comparative adhesive. The tools used included an infrared thermometer, a moisture meter for measuring water content, an anemometer for measuring air velocity, a stopwatch, a scale, and a briquette stove. The research findings indicate that honeycomb briquettes with 14 holes made from sago waste and coconut shells with damar resin as a binder exhibit faster combustion with a content level of approximately 10-12%. The conduction heat transfer in these briquettes is approximately 26,376 watts/m2, while the convective heat transfer reaches 40,801 watts. In comparison, the testing with tapioca flour as a binder shows a conduction value of 42,206 watts/m2 and convection of 43,208 watts. From these research results, briquettes made from sago waste and coconut shells with damar resin as a binder can be an effective alternative to replace kerosene fuel. The high combustion speed and efficient heat transfer make these briquettes attractive for alternative energy use